Electron Transfer Strategies to Regulate Carriers’ Separation for Intensive Pyroelectric Dynamic Therapy With Simultaneous Photothermal Therapy - Sun, Bingxia; Meng, Yun; Song, Tianlin; Shi, Jieyun; He, Xinhong; Zhao, Peiran (Frontiers in Chemistry, 2022)
The endogenic heat shock proteins and uneven local heat distribution are two main obstacles for tumor hyperthermia therapy strategy. This study designed Au-SnSe-PVP nanomaterials by modifying Au nanoparticles and biocompatible PVP on SnSe nanorods to solve these two problems with new ROS production strategy. The Au-SnSe-PVP nanomaterials with excellent photothermal conversion performance can produce thermoelectric effect in response to temperature difference during the photothermal conversion process. The modification of Au nanoparticles can attract free electron (e-) to accumulate and promote the separation of electrons and holes (h+) in thermoelectric process, thus further promotes e--rich Au nanoparticles induced H2O2 homolysis and h+-H2O half-reaction to generate hydroxyl radicals (•OH), realizing the synergistic application of photothermal therapy (PTT) and pyroelectric dynamic therapy (PEDT) in tumor treatment.